The Cosmic Horizon as the Highest Heaven: Examining Michael Guillen's Hypothesis - Belay Sitotaw Goshu; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2026)
The human tendency to locate the divine in spatial terms represents a cognitive universal, yet classical theism affirms divine transcendence, the claim that God as Creator cannot be contained within creation. Into this tension steps physicist Michael Guillen, who has proposed that the "highest heaven" described in biblical tradition possesses a specific physical location: the cosmic horizon, the boundary of the observable universe where galaxies recede at the speed of light and time ceases. This article critically examines Guillen's hypothesis, evaluating whether it successfully integrates scientific cosmology with theological claims about divine transcendence and the nature of heaven. The study employs interdisciplinary analysis, drawing on cosmological literature to clarify the scientific status of the cosmic horizon, and on theological sources (biblical, patristic, medieval, and contemporary) to assess the hypothesis against classical and modern understandings of divine transcendence, immanence, and eschatology. The analysis proceeds through comparative evaluation of scientific and theological frameworks. While Guillen's hypothesis has received popular attention, sustained scholarly analysis remains lacking. This article provides the first systematic examination of the proposal within the science-religion literature, demonstrating how the hypothesis reveals fundamental tensions between spatial models of divinity and theological commitments to transcendence. It offers a constructive alternative: interpreting the cosmic horizon as a symbol of transcendence rather than a literal location. Scientifically, Guillen misconstrues the cosmic horizon, which is not a physical location but an observer-dependent observational boundary. Theologically, his spatial literalism conflicts with classical theism's affirmation that God cannot be contained within creation (1 Kings 8:27; Augustine; Aquinas).